PEMBERDAYAAN WIRAUSAHA DALAM PENDEKATAN ADMINISTRASI PADA WAREHOUSING BISNIS DI RPTRA RAWABADAK SELATAN - Ramadani, Istifa; Hidajat, Koerniawan (Jurnal Abdimas Bina Bangsa, 2024)
In the business world, both for companies engaged in manufacturing and services, it is certainly very important to realize that the survival of the company is more important than just big profits. The purpose of warehousing administration is to optimize the use of available resources and ensure efficient warehouse operations. The warehousing administration process can help companies reduce costs and increase profits by optimizing warehousing processes and minimizing errors or losses. The method used in this community service activity is socialization regarding entrepreneurial empowerment in the administrative approach to business warehousing using a participatory approach by actively involving participants in discussions and interactions between participants and speakers. The results of the community service activities held on Saturday, July 20, 2024 showed that 90% of participants were able to ask several questions to the speakers and were able to answer the quizzes given by the speakers. So, it can be concluded that the delivery of the material given to the audience was effective, conducive and enthusiastic from the participants